Patterns and perceptions of newspaper reading among university of Ibadan students (2014)
The assumption that Nigerian youths do not read newspapers is misleading as far as current technological development is concerned. The paper argues that University of Ibadan students read newspapers regularly but mostly from digital media platforms. Anchored on aspects of Selectivity and Uses and Gratifications theories, data were retrieved through focus group discussion and in-depth interview and findings reveal that students' exposure to media is driven by the desire to gratify their socio-economic and information needs. Newspaper readership is limited to current news, entertainment, human-angle stories, news headlines and news bits while preference of online versions is attributed to accessibility, availability, affordability, flexibility, interactivity and currency of news. In line with existing transformation of the newspaper industry, the Internet and mobile phones are playing key roles in enhancing students' news seeking and reading behaviour; however, there exists gender differentials in frequency and content of newspaper readership. The paper concludes that digitalization has implications for newspaper reading among young people and points to the need for technological adaptation in a changing news landscape.